2019
DOI: 10.1021/acs.cgd.8b01194
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole: Synthesis and Structural Characterization of Four New Pharmaceutical Cocrystal Forms

Abstract: Pharmaceutical cocrystals have emerged over the past several decades as an alternative path for synthesizing stable and/or improved crystalline forms of active pharmaceutical ingredients. In this contribution, we developed a reproducible cocrystallization path for the supramolecular synthesis of four new pharmaceutical cocrystal forms of fluconazole (FLZ), an antifungal multifunctional drug: fluconazole–fumaric acid monohydrate (1:1:1), fluconazole–malic acid (1:1), fluconazole–dipicolinic acid (1:1), and fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Notably, this imidazolic alcohol (5f) contains two 2,4-dichloro-substituted benzene rings (2,4-Cl 2 Ph) similar to MCZ (Mangas-Sá nchez et al, 2011;Becher & Wirsel, 2012), which is also its constitutional isomer (Scheme 1). In addition, the presence of halogen atoms such as F or Cl seems to be key to the antifungal activity of the Nsubstituted 4-aryl-2-methylimidazoles studied (most azoles in clinical use possess halo-substituted benzene rings) (Borgers, 1980;Fromtling, 1988;Di Santo et al, 2005;Espinel-Ingroff, 2009;Strushkevich et al, 2010;Emami et al, 2017;White et al, 1998;Kathiravan et al, 2012;Shrestha et al, 2017;Kastelic et al, 2010;Tsutsumi et al, 2011;Dayo-Owoyemi et al, 2019;Pershing et al, 2002;Elewski & Vlahovic, 2014;Mangas-Sá nchez et al, 2011;Becher & Wirsel, 2012), since the polyhalogenated compounds [(4b), (4d) (Elejalde et al, 2018) and (5f)] presented the lowest IC 50 values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, this imidazolic alcohol (5f) contains two 2,4-dichloro-substituted benzene rings (2,4-Cl 2 Ph) similar to MCZ (Mangas-Sá nchez et al, 2011;Becher & Wirsel, 2012), which is also its constitutional isomer (Scheme 1). In addition, the presence of halogen atoms such as F or Cl seems to be key to the antifungal activity of the Nsubstituted 4-aryl-2-methylimidazoles studied (most azoles in clinical use possess halo-substituted benzene rings) (Borgers, 1980;Fromtling, 1988;Di Santo et al, 2005;Espinel-Ingroff, 2009;Strushkevich et al, 2010;Emami et al, 2017;White et al, 1998;Kathiravan et al, 2012;Shrestha et al, 2017;Kastelic et al, 2010;Tsutsumi et al, 2011;Dayo-Owoyemi et al, 2019;Pershing et al, 2002;Elewski & Vlahovic, 2014;Mangas-Sá nchez et al, 2011;Becher & Wirsel, 2012), since the polyhalogenated compounds [(4b), (4d) (Elejalde et al, 2018) and (5f)] presented the lowest IC 50 values.…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the hydroxyl group of (5) also favors intermolecular hydrogen bonds for directing the imidazolic and 2-arylethyl moieties in a parallel conformation, such as occurs in some azole drugs [Fig. 2(b)] (Kastelic et al, 2010;Tsutsumi et al, 2011;Dayo-Owoyemi et al, 2019). In our most recent work (Macías, Elejalde et al, 2018), a complete study by X-ray diffraction of the electronic effects of the 4-aryl substituent of NH-imidazoles (3a)-(3c) and their in vitro antifungal evaluation was reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the study of solid-state pharmaceutical chemistry, including cocrystals, salts, polymorphs, and solvates, has been extensively applied in the area of pharmaceutical technology [1][2][3][4][5]. Thus, the design of pharmaceutical solid forms of drugs has become an important step in the pharmaceutical process [6].…”
Section: Introductionmentioning
confidence: 99%